Insilico evaluation of isatin-based derivatives with RNA-dependent RNA polymerase of the novel coronavirus SARS-CoV-2. Issue 15 (29th August 2022) - M., Rajesh Kumar; Gideon, Daniel A.; Mariadasse, Richard; Nirusimhan, Vijay; A., Sherlin Rosita; Edward, Jesu Castin; Jeyaraman, Jeyakanthan; Dhayabaran, Violet
Abstract: Isatin (1H-indole-2, 3-dione)-containing compounds have been shown to possess several remarkable biological activities. We had previously explored a few isatin-based imidazole derivatives for their predicted dual activity against both inflammation and cancer. We explored 47 different isatin-based derivatives (IBDs) for other potential biological activities using in silico tools and found them to possess anti-viral activity. Using AutoDock tools, the binding site, binding energy, inhibitory constant/ K i and receptor-ligand interactions for each of the compounds were analyzed against SARS-CoV-2 RNA-dependent RNA polymerase (RdRp). The partition coefficient (logP) values were predicted using MedChem Designer tool. Based on the best K i, binding energy and the ideal range of logP (between 1.0 and 3.0), 10 out of total 47 compounds were deemed to be prospective RdRp inhibitors. Some of these compounds gave better K i, binding energy and logP values when compared to standard RdRp inhibitors, such as remdesivir (REM) ( K i = 15.61 μM, logP = 2.2; binding energy = −6.95), a clinically approved RdRp inhibitor and nine other RdRp inhibitors. The results showed that the 10 selected IBDs could be further explored. Molecular dynamics simulations (MDSs) showed that the selected RdRp-IBD complexes were highly stable compared to the native RdRp and RdRp-REM complex during 100 ns time periods. DFT studies were performed for the compounds 16a, 24a, 28a, 38a and 40a, to evaluate the charge transfer mechanism for the interactions between the IBDs and the RdRp residues. Among these, ADME profiling revealed that 28a is a possible lead compound which can be explored further for anti-RdRp activity in vitro . Communicated by Ramaswamy H. Sarma